Resistance exercise overtraining and overreaching. Neuroendocrine responses - Fry, A. C.; Kraemer, W. J. (Sports Medicine, 1997)
Overtraining is defined as an increase in training volume and/or intensity of exercise resulting in performance decrements. Recovery from this condition often requires many weeks or months. A shorter or less severe variation of overtraining is referred to as overreaching, which is easily recovered from in just a few days. Many structured training programmes utilise phases of overreaching to provide variety of the training stimulus. Much of the scientific literature on overtraining is based on aerobic activities, despite the fact that resistance exercise is a large component of many exercise programmes. Chronic resistance exercise can result in differential responses to overtraining depending on whether either training volume or training intensity is excessive. The neuroendocrine system is a complex physiological entity that can influence many other systems. Neuroendocrine responses to high volume resistance exercise overtraining appear to be somewhat similar to overtraining for aerobic activities. On the other hand, excessive resistance training intensity produces a distinctly different neuroendocrine profile. As a result, some of the neuroendocrine characteristics often suggested as markers of overtraining may not be applicable to some overtraining scenarios. Further research will permit elucidation of the interactions between the neuroendocrine system and other physiological systems in the aetiology of performance decrements from overtraining.